Greening the Financial Sector: How to Mainstream Environmental Finance in Developing Countries - Köhn, Doris (Springer Nature, 2012)
Macroeconomics/Monetary Economics//Financial Economics; Finance, general; Environmental Economics; Development Finance; Energy Efficiency; Environmental Finance; Green Energy Finance; Renewable Energy